The Relation between Mathematical Connection Abilities and Mathematical Problems Solving Skill of Cadet - Agustina, Eka Nurmala Sari; Sari, Tri Hariyati Nur Indah; Novitasari, Novitasari (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
This study aims to identify the relationship between mathematical connection ability (MCA) and mathematical problem-solving skills (MPSS) in cadets of the Ship Operation Engineering Technology Study Program at the Surabaya Maritime Polytechnic. Using a quantitative descriptive approach, 21 cadets were given two questions designed to measure MCA and MPSS, which were then analyzed using descriptive statistics and the Spearman rank correlation test. The results showed a significant positive correlation between MCA and MPSS, with a coefficient value of 0.901. This finding indicates that cadets with higher MCA tend to have better problem-solving skills. Additionally, cadets experienced difficulties with questions involving trigonometric concepts in a nautical context, such as the use of compass points and distance calculations. This study highlights the importance of strengthening MCA and MPSS in maritime vocational education to enhance cadets' technical and cognitive skills, particularly in solving complex operational problems in the maritime sector.